Karakteristik Kimia dan Daya Simpan Susu Kambing Pasteurisasi dengan Penambahan Ekstrak Jambu Biji Merah (Psidium guajava L.) - Raka Raihan; Aaf Falahudin; Lili Adam Yuliandri (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
The aim of this research is to analyze the effect of adding red guava extract on the chemical characteristics and shelf life of pasteurized goat milk with the addition of red guava extract (Psidium guajava L). This research was carried out using an experimental method using a completely randomized design consisting of 5 treatments and 4 replications. Chemical characteristics were carried out using quantitative descriptive methods. The treatment used was the addition of 0%, 3%, 6%, 9% and 12% red guava extract. The research results showed that the chemical characteristics of pasteurized goat's milk with the addition of red guava extract were the highest water content at P4, 82.91% and the lowest at P3, namely 81.32%, the highest ash content at P1, 1.01% and the lowest at P4, namely 0 .76%, the highest protein content at P1 3.65% and the lowest at P3, namely 3.14%, the highest fat content at P0 4.73% and the lowest at P4, namely 4.32%, the highest carbohydrate content at P3 10.28 % and the lowest was in P4, namely 8.74%, and the highest vitamin C level was in P4, 35.03 mg/100g and the lowest was in P1, namely 26.29 mg/100g. The shelf life of goat milk at 11°C at P0, P1 and P2 is up to 5 days of storage, while for P3 and P4 it can be stored for 3 days. The conclusion is that P1 is the best treatment in producing the chemical characteristics of pasteurized goat's milk, while P4 is the treatment that produces the highest levels of vitamin C.